Value of immunohistochemistry in the detection of BRAFV600E mutations in fine‐needle aspiration biopsies of papillary thyroid carcinoma. Issue 1 (4th September 2013) - Zimmermann, Anne‐Katrin; Camenisch, Ulrike; Rechsteiner, Markus P.; Bode‐Lesniewska, Beata; Rössle, Matthias
Abstract : BACKGROUND: Fine‐needle aspiration biopsy (FNAB) is important in the diagnostic establishment of suspicious thyroid nodules. In thyroid neoplasms, mutation of the BRAF gene occurs rather exclusively in papillary thyroid carcinoma (PTC) and results in > 98% of the cases in V600E amino acid substitution. In the current study, the authors investigated the diagnostic value of a recently described monoclonal antibody that detects this specific mutation on FNAB specimens from patients with PTC. METHODS: BRAF V600E status of FNAB cell blocks from 55 patients with PTC was analyzed by immunohistochemistry (IHC) with the new BRAF V600E antibody (clone VE1) and by Sanger sequencing (SaS). In discrepant cases, ultra‐deep sequencing was also performed. Available corresponding histological specimens were investigated by IHC and, in selected cases, with SaS as well. RESULTS: All cases yielded evaluable IHC staining results of the cell block sections with good interobserver agreement (kappa value, 0.650). Ten tumors (18.2%) demonstrated no staining, 10 tumors (18.2%) demonstrated equivocal staining, 25 tumors (45.4%) demonstrated moderate staining, and 10 tumors (18.2%) demonstrated strong staining. SaS was able to be performed in 48 cases. Nineteen cases demonstrated wild‐type BRAF and 29 cases were found to have the BRAF V600E mutation. After performing ultra‐deep sequencing 1 false‐positive and 2 false‐negative VE1 IHC cases remained, resulting in a sensitivity of 93.8% and a specificity of 93.8%. CONCLUSIONS: BRAF V600E mutations in FNAB specimens from patients with PTC can be reliably detected in most cases by IHC with a new mutation‐specific antibody. Interpretation of VE1 IHC staining results on cell block slides of PTC can be difficult in some cases. Cancer (Cancer Cytopathol) 2014;122:48–58 . © 2013 American Cancer Society . Abstract : The BRAF V600E mutation can be reliably detected in most cell block specimens of fine‐needle aspiration biopsies of papillary thyroid carcinoma by immunohistochemistry using a new mutation‐specific antibody. This new antibody may be a useful alternative to polymerase chain reaction‐based methods in the detection of BRAF V600E mutations on cytological cell block specimens.